How to measure industrial relations climate in Chinese context - Deng, J.; Chan, D.; Yang, S.; Caudwell, Kim (2015)
The employees’ perception of the industrial relations climate is essential to promote the development of enterprise, maintain social stability and human being’s psychological well-being. With the development of China’s economy, the complexities exist in the Chinese market may lead to some potential issues toward the industrial relations. Therefore, the need to understand the nature of the industrial relations in the Chinese market is crucial to the various stakeholders. The present study aimed to develop a psychometric scale measuring the Chinese industrial relations through three consecutive studies. The research was conducted from one hundred twenty-two enterprises across four different industries including manufacturing, software services, pharmacy and serving, with 3259 employees. The developed scale contains five psychological factors including interactiveness, motivation, harmony, careness and fairness, and the results supported the sound psychometric properties of the Industrial Relations Climate Scale.